Justiça, prazer e sofrimento no trabalho: um estudo com jovens trabalhadores assistidos pelo ESPRO-BH - Samara de Menezes Lara (2019)
Work plays a fundamental role in society and its concept has been discussed in academic forums through its constant changes reflection and also through its impacts on workers. During the last decades of the twentieth century, the capitalist productive process has undergone changes that demand more and more production with high quality and low cost, aiming high competitiveness. These ongoing changes have outlined significant transformations in the world of work and direct impacts on labor relations (MENDONÇA; MENDES, 2005; LANCMAN, 2008; ANTUNES; PRAUN, 2015). In this context of structural precariousness of work (ANTUNES, 2008, 2009) organizations can develop new management models that affect their workers related to the distribution of resources and rewards, the rules to be followed and their interpersonal relationships (SOUSA; MENDONÇA, 2009; FRANCO; PAIVA, 2018), so that workers may see themselves as wronged if they do not perceive fairness and clarity in these processes (LIMA, 2011). However, labor relations may have different contours in audiences identified with diversity, such as young workers (FRANCO, et al., 2017, BARBOSA, 2018). The young workers are benefited by the law of the young apprentice and the target audience of this research are those who attended the Association of Vocational Social Teaching (ESPRO) of Belo Horizonte, in the year 2018. Faced with such scenario, we have as a general objective to understand how the dimensions of organizational justice is related to the experiences of pleasure and suffering in the work of young workers assisted by Belo Horizonte ESPRO, in their own perception. To do so, we sought to evaluate and describe the constructs: organizational justice based on the proposals of Rego (2002), Rego et al. (2002) and Mendonça (2003); and pleasure and suffering with reference to the works of Dejours (2004, 2007, 2008), Mendes (2007) and Mendes and Ferreira (2007), as well as other references that address such constructs. After the theoretical basis, a qualitative and quantitative research was done with the purpose of complementarity in order to maximize the strengths and minimize the weaknesses of bought methods (CRESWELL, 2007; JOHNSON; ONWUEGBUZI, 2004). The research was considered descriptive, from the field, developed through a case study. The data collection was carried out concomitantly: in the quantitative approach 664 questionnaires were collected and in the qualitative 23 interviews with a semi-structured script. Data from the questionnaires were treated using uni, bivariate and multivariate descriptive statistical analysis and the interviews were analyzed by content analysis. As a result, the perceptions of the subjects regarding the decision-making processes (procedural justice), the distribution of goods and rewards (distributive justice), and the interpersonal relations between them and the superior (interactional justice) positively influence the experiences of pleasure and negatively at suffering experiences at work, been these data corroborated by qualitative analysis.